PENGARUH MOTOR EDUCABILITY TERHADAP KETERAMPILAN BERMAIN BOLA BASKET DALAM PENDIDIKAN JASMANI SISWA SEKOLAH MENENGAH PERTAMA - Rahmadanti; Abdul Salam Hidayat; Tedi Purbangkara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine, analyze, and identify the influence of motor educability on basketball playing skills in physical education among junior high school students. This research was conducted on the basketball court of SMP Negeri 6 Karawang Barat, involving students from class VIII G. The study employed an experimental method. Sampling was done using purposive sampling technique based on predetermined criteria, with a total of 39 students selected as participants. The instrument used was the Game Performance Assessment Instrument (GPAI). The results of this study show a significant effect, as evidenced by the increase in the average pretest score of 1.92 to a posttest average of 3.99 after the treatment was administered. This is also supported by the results of the paired sample t-test, which showed a significance value of 0.000 (Sig. 2-tailed < 0.05), indicating a statistically significant difference between the pretest and posttest scores. This means there was a notable improvement in performance after the treatment. The effect is reflected in the increased influence of motor educability on basketball playing skills in physical education for junior high school students.